Genomic Insights into the Correlation between Gut Microbiota and Dehagni A Review - prabhakaran, Vidhya; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2024)
The human gut microbiota is rich in diverse microbes like bacteria, archaea and eukaryote colonizing the entire Gastro Intestinal Tract and the genes encoded by these resident bacteria constitutes the microbiome. The gut microbiome participates in vital processes including digestion, energy homeostasis and metabolism, the synthesis of vitamins and other nutrients, and the development and regulation of immune function. A balanced and diverse microbiome is critical for maintaining health and immunological balance. Dysbiosis arises when the delicate and elaborate ecology of microbial communities are disrupted by internal or external factors. Famous for saying that "all disease begins in the gut," Hippocrates is regarded as the founder of contemporary western medicine. An appropriate diet, healthy digestion, and a holistic way of living are all highly valued in Ayurveda. Agni converts food in the form of energy, which is responsible for all the vital functions of our body. When the Agni of an individual is Sama, then that person would be absolutely healthy and would lead a long, happy, healthy life. But, if the Agni of a person is vitiated, the whole metabolism in his body would be disturbed, resulting in ill health and disease. Hence, Agni is said to be the base (mool) of life. Understanding the genomic factors that influence the gut microbiota can shed light on how it affects Agni. Genomic insights in to the correlation between gut microbiota and Agni have provided valuable information about the role of the microbiota in maintaining a healthy digestive system.